Community structure of soil phototrophs along environmental gradients in arid Himalaya. (6th May 2013) - Janatková, Kateřina; Řeháková, Klára; Doležal, Jiří; Šimek, Miloslav; Chlumská, Zuzana; Dvorský, Miroslav; Kopecký, Martin
Summary: The well‐developed biological soil crusts cover up to 40% of the soil surface in the alpine and subnival zones of the Tibetan Plateau, accounting for a vast area of Asia. We investigated the diversity and biomass of the phototrophic part (Cyanobacteria) of the microbial community inhabiting biological soil crusts and uncrusted soils in their surroundings on the elevation gradient of 5200–5900 m a.s.l. The influence of soil physico‐chemical properties on phototrophs was studied. The ability of high‐altitude phototrophs to fix molecular nitrogen was also determined under laboratory conditions. The biological soil crust phototroph community did not differ from that living in uncrusted soil in terms of the species composition, but the biomass is three‐to‐five times higher. An increasing trend in the cyanobacterial biomass from the biological soil crusts with elevation was observed, with the genera Nostoc spp., Microcoleus vaginatus and Phormidium spp. contributing to this increase. Based on the laboratory experiments, the highest nitrogenase activity was recorded in the middle elevations, and the rate of nitrogen fixation was not correlated with the cyanobacterial biomass.